Measuring Efficiency Model of Woman Existence on Political Party - Puspitasari, Dinarjati Eka; Kumalasari, Ratna Dewi (EP FEB UNS, 2017)
This research has measured the existence of woman on the political party. The existence and effect can be analysed with Data Envelopment Analysis (DEA) model. DEA model can analys the effeciency of woman existent on political party. This model also makes decision to choose its optimal effect.The result of this research consist of two aspects, the first is the efficiency of woman existence on political party. This first aspect can be a based to choose its optimal effect. And the second aspect is making the process to gain optimal condition for the party which have used woman (example:as party or legislative members). The two aspects of the result can be recommended as a way to manage existence of woman on the political parties. The policies will be hoped to construct policies to gain optimal condition for the political parties which have used woman as the candidate of legislative members. Keywords: Efficiency model, Woman Existence, Political Party, Data Envelopment Analysis (DEA).JEL Classification: Q55, Q56